Angiosarcoma of the seminal vesicle: a case report of long-term survival following multimodality therapy - Kenneth Chang; Terence T. Sio; Vishal S. Chandan; Matthew J. Iott; Christopher L. Hallemeier (Rare Tumors, 2014)
Angiosarcoma of the seminal vesicle is an extremely rare malignancy, with few published case reports in the literature. We present a case of primary angiosarcoma of the seminal vesicle in a 45-year-old male who was treated with multimodality therapy, consisting of neoadjuvant chemotherapy and chemoradiation followed by surgical resection and intraoperative radiation therapy. He has been free of cancer recurrence for more than six years after completion of therapy. To our knowledge, this represents the longest reported survival of a patient with this rare tumor, and one of the few cases reported using a multimodality therapy approach.